1998
DOI: 10.1128/mcb.18.5.3059
|View full text |Cite
|
Sign up to set email alerts
|

Laron Dwarfism and Non-Insulin-Dependent Diabetes Mellitus in the Hnf-1α Knockout Mouse

Abstract: Mice deficient in hepatocyte nuclear factor 1 alpha (HNF-1␣) were produced by use of the Cre-loxP recombination system. HNF-1␣-null mice are viable but sterile and exhibit a phenotype reminiscent of both Laron-type dwarfism and non-insulin-dependent diabetes mellitus (NIDDM). In contrast to an earlier HNF-1␣-null mouse line that had been produced by use of standard gene disruption methodology (M. Pontoglio, J. Barra, M. Hadchouel, A. Doyen, C. Kress, J. P. Bach, C. Babinet, and M. Yaniv, Cell 84:575-585, 1996)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
241
0
3

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 247 publications
(252 citation statements)
references
References 41 publications
(65 reference statements)
8
241
0
3
Order By: Relevance
“…Mice deficient in HNF1α exhibit a phenotype reminiscent of both Laron dwarfism and non-insulin dependent diabetes mellitus (NIDDM) (3). HNF1α-null mice are viable yet sterile and exhibit retarded growth (3). A fraction of HNF1α-null mice die shortly after weaning.…”
Section: Introductionmentioning
confidence: 99%
“…Mice deficient in HNF1α exhibit a phenotype reminiscent of both Laron dwarfism and non-insulin dependent diabetes mellitus (NIDDM) (3). HNF1α-null mice are viable yet sterile and exhibit retarded growth (3). A fraction of HNF1α-null mice die shortly after weaning.…”
Section: Introductionmentioning
confidence: 99%
“…However, a previous study using RT-PCR suggested that PDX-1 expression was reduced in HNF-1α (-/-) mice [47]. Since the number of beta cells is decreased in the islets of HNF-1α null mice [15,16], a reduced number of beta cells that express PDX-1 might be a possible explanation for the reduced expression of PDX-1 in the islets. Secondary down-regulation of PDX-1 by hyperglycaemia [38,39] might also account for the discrepancy.…”
Section: Discussionmentioning
confidence: 91%
“…Consecutive sections (6 µm thick) were cut and collected on glass slides for examination. Transgenic mice with a dominant negative overexpression of mutant human HNF-1α (P291fsinsC-HNF-1α) in beta cells and HNF-1α null mice have been described [16,18,19]. The experimental protocol was approved by the Ethics Review Committee for Animal Experimentation of Osaka University.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, HNF1␣-null mice are dwarf and diabetic. 22 While global analysis of gene expression by microarray was not reported, what is most surprising from the current study is the small number of genes that have altered expression in liver of ␤-catenin liver-null mice. In addition to Glu1, Cyp1a2 and Cyp2e1, expression of the glutamine transporter, ornithine aminotransferase, ammonia transporter, and RhBG genes are also virtually extinguished in these mice.…”
mentioning
confidence: 82%